Experimental Study of the Thermal Properties of a Homogeneous Dispersion System of a Paraffin-based Composite Phase Change Materials. (April 2021) - Wu, Xuehong; Gao, Maotiao; Wang, Kai; Wang, Qiangwei; Cheng, Chuanxiao; Zhu, Youjian; Zhang, Fangfang; Zhang, Qi
Highlights: Proposed a method of preparing a homogeneous dispersion system of a paraffin-based composite PCM Explored the dispersion method of carbon nano particles in oily liquid Carbon nano particles fillers are used to enhance the thermal conductivity in PCM. Thermal properties of two types of PCMs are comprehensively analyzed. ABSTRACT: Paraffin is widely used in medium- and low-temperature storage because of its excellent properties. To improve thermal conductivity of paraffin, carbon nanomaterials filler with high thermal conductivity was gradually added to. In this paper, composite phase change materials (PCMs) composed of cold storage paraffin with a phase transition temperature of 4°C and two types of high thermal conductivity nanoparticles, graphene nano-platelets (GNPs) and carbon nanotubes (CNTs), were selected and prepared by mechanical separation with a suitable dispersant. The relationship between thermal conductivity and standing time of two composite PCMs revealed that the thermal conductivity of the composite PCMs of GNPs/paraffin and CNTs/paraffin remained stable at room temperature for 20 days and 40 days, respectively. When the mass fraction of GNPs or CNTs is 5%, the thermal conductivities of the composites, which are 0.266 W / ( mÂ·K ) and 0.250 W / ( mÂ·K ), respectively, increase the most. Compared to those of pure paraffin and the CNTs/paraffin composites, the DSC curves of the GNPs/paraffin composites moved forward due to the higher thermal conductivity of the composite PCMs, which was more accurate for the experimental operation procedure. Due to the different structure and arrangement of particles, the latent heat of CNTs/paraffin was slightly lower than that of GNPs/paraffin with the same mass fraction of paraffin. The composites exhibited stable and excellent phase transition characteristics after 100 melting and solidification cycle tests.